Estruturação da assembléia de insetos aquáticos em ambiente epígeo e hipógeo - Martins, Vanessa Mendes (2016)
The environmental stability of the cave environment, as well as the simplicity of their communities, gives this environment the status of a natural laboratory. Therefore, this ecosystem offers a unique opportunity for ecological studies. However, knowledge about the ecological structuring of the community in the subterranean environment is still incipient, especially in the case of aquatic organisms. Therefore, benthic macroinvertebrates were collected with a surber collector in a hypogean and epigean sections of the Pai João river in the Lapa Grande State Park, Montes Claros, MG. The objectives of the present study were to understand how the assembly of aquatic insects in the cave environment is structured, as well as to compare it to the epigean assembly in order to verify differences between environments. A total of 1566 individuals were collected, of which 1458 belonged to the epigean environment, 8 in the ecotonal region and 100 to the hypogeum. The lower diversity in the hypogean environment was due to the innumerable restrictions of the cave environment. The organisms Hexacylloepus sp. and Heterelmis sp. avoided niche overlap via differentiation of body size and environmental preferences in the cave environment. However, in the epigean environment Hexacylloepus sp. and Heterelmis sp. body sizes overlap, most likely because there is no competition facing the abundance of trophic resources. According to RLQ analysis the species distribution does not occur as a function of the functional attributes. However, the fourth-corner analysis demonstrated that some functional attributes of the aquatic insect assembly were significantly related to environmental variables. Functional diversity (α) in the hypogean environment (38.3) was lower than in the epigean (57.8). Such differences between the epigean and hypogean environments demonstrate that the cave environment acts as an environmental filter, drastically reducing functions in the subterranean environment. Results such as these demonstrate that the dynamics of the aquatic insect assembly in the subterranean environment is distinct from the epigean, so understanding the peculiarities of the cave environment is extremely useful for mitigation and conservation actions of these environments.